Rapid isolation and characterization of Wharton's jelly-derived mesenchymal stem cells maintained in fresh-prepared human AB-serum - Tjahjono, Yudy; Dewi, Sianty; Novita, Bernadette Dian; Wijaya, Hendy; Putra, Brilliant Dwi; Kuncorojakti, Suryo; Hendriati, Lucia; Jong, FX Himawan Haryanto; Widodo, Teguh; Malonda, Franklin Vincentius (Universa Medicina, 2025)
Background Mesenchymal stem cells (MSCs) are valued in regenerative medicine for their multipotency, proliferative capacity, and immunomodulatory properties. Wharton’s jelly-derived MSCs (WJ-MSCs) from the umbilical cord offer a non-invasive, promising source for clinical applications, because easy isolation, lack of ethical concerns, and the presence of both embryonic and adult stem cells have made them a valuable source for use in therapeutic applications and regenerative medicine. This study aimed to optimize WJ-MSC isolation and characterization methods. Methods Human umbilical cords from three healthy donors were collected post-cesarean under strict inclusion criteria. WJ-MSCs were isolated using the explant culture method, with cells adhering to T75 flasks pre-coated with 2% gelatin. Cultures were maintained in Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% freshly prepared Human AB serum and monitored for 21 days. Flow cytometry (BD FACSAria) was performed at passages 1 and 5 to assess MSC markers CD105, CD73, CD90, and CD44, alongside the exclusion marker CD45. Results WJ-MSCs exhibited fibroblast-like morphology by passage 1 and showed robust proliferation. Flow cytometry revealed high CD44 expression (~60%) at passage 1, while CD105, CD73, and CD90 became prominent by passage 5. CD45 remained low, suggesting minimal hematopoietic contamination. Conclusion This study confirms the feasibility of isolating and expanding WJ-MSCs using DMEM with 10% human AB serum. While consistent cell growth was achieved, the 21-day culture period may require optimization for scalability, including serum concentration, substrate coatings, and oxygen levels. CPJ-MSCs may be preferable for applications demanding rapid expansion and early marker expression.